The Finnish logophoric pronoun hän: A quantitative approach - Katri Priiki (Estonia, 2022)
The paper examines the logophoric use of hän ‘he/she’ in contemporary
Finnish conversation data. A logophoric pronoun is a device used in reported speech
referring to the original speaker of a reported utterance. In informal spoken Finnish the pronoun hän is mostly used logophorically, even though in Standard Finnish, it is the regular third person personal pronoun. The paper approaches the logophoric function of hän from a new, quantitative viewpoint by examining the frequency of different aspects of the logophora. Based on the quantitative analysis of the data, the canonical
construction of indirect speech seems to be the most typical context for the pronoun hän to occur, even though previous studies have claimed Finnish logophora semantic rather than structural. From the prototypical position the logophoric use spreads to reporting thoughts, interpreting feelings, and expressing the roles of the participants of the interaction.
Keywords: logophora, personal pronouns, pronouns, reported speech, spoken language,
third person, Finnish